2018
DOI: 10.1016/j.jpainsymman.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Relating to the Experience of Contingency in Patients With Advanced Cancer: An Interview Study in U.S. Patients

Abstract: Context. Being diagnosed with incurable cancer can be a life-changing experience, evoking different spiritual questions and needs. Confronting a serious life-threatening event occurs not only often unexpected but also can disrupt a person's selfimage and ideals of their personhood. This confrontation makes it difficult for people to integrate it into their personal life storydotherwise referred to as an experience of contingency. Objectives. Different modes of relating to the contingent life event of having ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…Yvonne Weeseman, Hanneke van Laarhoven and Michael Scherer-Rath challenge these divisions. In their research on highly sensitive children they confirm the findings of Kruizinga et al (2017;2018), who distinguish between four modes of dealing with experiences of contingency, namely denying, acknowledging, accepting and receiving. They assume that immanent agnostic forms of acceptance and receiving contingency do not automatically eliminate contingency, as Wuchterl claims with his dogmatic appeal to universal autonomous reason, but rather characterise open attempts at interpretation.…”
supporting
confidence: 65%
“…Yvonne Weeseman, Hanneke van Laarhoven and Michael Scherer-Rath challenge these divisions. In their research on highly sensitive children they confirm the findings of Kruizinga et al (2017;2018), who distinguish between four modes of dealing with experiences of contingency, namely denying, acknowledging, accepting and receiving. They assume that immanent agnostic forms of acceptance and receiving contingency do not automatically eliminate contingency, as Wuchterl claims with his dogmatic appeal to universal autonomous reason, but rather characterise open attempts at interpretation.…”
supporting
confidence: 65%
“…Recently, we found that although four different modes of relating to contingency that we found in a Dutch study population can also be found in an American advanced cancer patient population, differences were found in the extend by which American patients described the fourth mode of relating to contingency, that is, the “receiving” mode. 59,60 This could suggest that American patients could be more open to the intervention that we developed. Furthermore, the generalization of our results may be limited by an overrepresentation in our study population of patients who are willing to talk about their life.…”
Section: Discussionmentioning
confidence: 99%
“…But, this limitation can be overcome if the content analysis is applied to transcripts of interviews or focus groups (Graneheim et al, 2017). This is proven by Kruizinga et al (2018), who used directed content analysis to extend their semi-structured interview model of spiritual care with cross-cultural perspectives drawn from interviews. Ngai et al (2020) also analyzed the contents of 608 Covid-19 posts to develop an integrated framework that governments can use to engage the public regarding the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some characterized it as either qualitative or quantitative content analysis (Godskesen et al, 2013). Some specified the type of content analysis approach that they used (Kruizinga et al, 2018;Shafiq & Kiran, 2018). Some studies were vague in describing their content analysis steps, such as one study which stated that their content analysis is quantitative and rhetorical in different sentences, yet did not clearly distinguish them (Shafiq & Kiran, 2018) and another study which mentioned that they used content analysis for the first phase of a study and then "a more detailed content analysis" for the next phase (Mahrt & Puschmann, 2014, p.10).…”
Section: Literature Reviewmentioning
confidence: 99%